2021
DOI: 10.1186/s12939-021-01425-2
|View full text |Cite
|
Sign up to set email alerts
|

Private health care market shaping and changes in inequities in childhood diarrhoea treatment coverage: evidence from the analysis of baseline and endline surveys of an ORS and zinc scale-up program in Nigeria

Abstract: Background Nearly 90,000 under-five children die from diarrhoea annually in Nigeria. Over 90% of the deaths can be prevented with oral rehydration salt (ORS) and zinc treatment but coverage nationally was less than 34% for ORS and 3% for zinc with wide inequities. A program was implemented in eight states to address critical barriers to the optimal functioning of the health care market to deliver these treatments. In this study, we examine changes in the inequities of coverage of ORS and zinc o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Programs that include price subsidies for example for ACT commodities, ORS Zinc, other child health commodities and programs which have utilized the integrated community case management strategy at drug shops have also been shown to be extremely effective. (Opiyo et al, 2016, Tougher et al, 2012, Tougher et al, 2014, Awor et al, 2018, Awor et al, 2014b, Braimoh et al, 2021). See table 2 for detailed information on studies and recommendations on utilizing drug shops for stronger health systems.…”
Section: Resultsmentioning
confidence: 99%
“…Programs that include price subsidies for example for ACT commodities, ORS Zinc, other child health commodities and programs which have utilized the integrated community case management strategy at drug shops have also been shown to be extremely effective. (Opiyo et al, 2016, Tougher et al, 2012, Tougher et al, 2014, Awor et al, 2018, Awor et al, 2014b, Braimoh et al, 2021). See table 2 for detailed information on studies and recommendations on utilizing drug shops for stronger health systems.…”
Section: Resultsmentioning
confidence: 99%
“…While our study design could not disaggregate which component(s) of the model contributed most to the increased uptake of ORS and zinc and which should be improved or removed, this type of systems package of interventions has a theoretical basis for being stronger than its component parts 69. Recent research focused on improving access to diarrhoea treatments in Nigeria, for example, also found that shaping the market system for ORS and zinc was effective in equitably improving coverage of the combination therapy 70. Future research may be conducted to assess the specific contributions of individual components of such an approach.…”
Section: Discussionmentioning
confidence: 98%
“…This is due to the fact that low-income households in LMICs, such as those in Africa, particularly in East Africa, cannot afford the expenses of healthcare services, including ORS and zinc. Thus, when children from low-income households get diarrhoea, they might not receive ORS with zinc 40…”
Section: Discussionmentioning
confidence: 99%